2013
DOI: 10.1371/journal.pone.0070355
|View full text |Cite
|
Sign up to set email alerts
|

Gβ-Like CpcB Plays a Crucial Role for Growth and Development of Aspergillus nidulans and Aspergillus fumigatus

Abstract: Growth, development, virulence and secondary metabolism in fungi are governed by heterotrimeric G proteins (G proteins). A Gβ-like protein called Gib2 has been shown to function as an atypical Gβ in Gpa1-cAMP signaling in Cryptococcus neoformans. We found that the previously reported CpcB (cross pathway control B) protein is the ortholog of Gib2 in Aspergillus nidulans and Aspergillus fumigatus. In this report, we further characterize the roles of CpcB in governing growth, development and toxigenesis in the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…SvfA is involved in ST biosynthesis and development, both of which are known to be functionally interconnected 4 . CpcB, a Gβ-like protein, governs diverse cellular events such as germination, growth, development, and ST synthesis 32 . Similar to the ΔsvfA strain, the cpcB deletion strain produced small and fragile cleistothecia with no ascospores and showed upregulation of veA and nsdD expression during sexual development 32 , suggesting a possible interaction between SvfA and CpcB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SvfA is involved in ST biosynthesis and development, both of which are known to be functionally interconnected 4 . CpcB, a Gβ-like protein, governs diverse cellular events such as germination, growth, development, and ST synthesis 32 . Similar to the ΔsvfA strain, the cpcB deletion strain produced small and fragile cleistothecia with no ascospores and showed upregulation of veA and nsdD expression during sexual development 32 , suggesting a possible interaction between SvfA and CpcB.…”
Section: Discussionmentioning
confidence: 99%
“…CpcB, a Gβ-like protein, governs diverse cellular events such as germination, growth, development, and ST synthesis 32 . Similar to the ΔsvfA strain, the cpcB deletion strain produced small and fragile cleistothecia with no ascospores and showed upregulation of veA and nsdD expression during sexual development 32 , suggesting a possible interaction between SvfA and CpcB. When levels of cpcB gene expression in the ΔsvfA strain and svfA gene expression in the ΔcpcB strain were studied during sexual development, cpcB expression was not affected by the lack of SvfA and in turn svfA expression was not affected in ΔcpcB mutants (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the cAMP/PKA pathway regulates the synthesis of several virulence factors [ 71 ]. In both A. nidulans and A. fumigatus , Rack1 proteins, CpcB, play important roles in fungal growth, conidiation, conidial germination, and mycotoxin production ( Table 1 ) [ 49 , 50 ]. In A. nidulans , CpcB represses the cross-pathway control in the presence of amino acids and regulates sexual development [ 50 , 52 ].…”
Section: Rack1 Proteins In Pathogenic Fungimentioning
confidence: 99%
“…Based on bioinformatics analyses, CpcB is highly conserved in eukaryotes with Gβ-like homologs exhibiting identities ranging from 60.4 to 95.6% ( Cai et al, 2015 ). Previous studies have demonstrated that CpcB plays important roles in hyphal growth and conidiation in A. fumigatus ( Kong et al, 2013 ; Cai et al, 2015 ). Despite its important functions, the molecular characterization of CpcB has not been performed.…”
Section: Introductionmentioning
confidence: 99%